In vitro anti-urease, antioxidant activities and phytochemical composition of Geranium purpureum - TAŞKIN, TURGUT (SPRINGER, 2017)
The aim of this study was to evaluate for the first time phenolic compounds amount, antioxidant and anti-urease effects of ethanol extract from Geranium purpureum aerial parts. Also the phenolic compounds in the ethanol extract were analysed by HPLC-DAD and confirmed by liquid chromatography with quadrupole time-of-flight mass spectrometry using targeted MS/MS techniques with accurate mass measurement. The phenolic compounds were identified as caffeic acid derivative, quinic acid, galloyl-hexoside, malic acid, gallic acid, methyl gallate hexoside, chlorogenic acid, caffeic acid, rutin, dicaffeoyl quinic acid and quercetin. In the present study, the results of all three antioxidant assays showed that the ethanol extract had higher DPPH and ABTS radical scavenging activity than ascorbic acid and BHT. In addition, according to the results obtained, ethanol extract showed moderate metal chelating and anti-urease activity. Therefore, ethanol extract can be used in both medicine and food industry as a natural antioxidant and anti-urease agents in the future.
Keywords: Geranium purpureum; Antioxidant; Antiurease; ESI-Q-TOF LC/MS; PHENOLIC-ACIDS; L.; FLAVONOIDS; CAPACITY; EXTRACTS